2020
DOI: 10.1002/jclp.23049
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility trial of the dialectical behavior therapy skills training group as add‐on treatment for adults with attention‐deficit/hyperactivity disorder

Abstract: Objective Our aim was to explore the feasibility, and efficacy of a Dialectical Behavior Therapy Skill Training Group (DBT‐ST) as an add‐on treatment for adult attention‐deficit/hyperactivity disorder (ADHD) in Latin America. Method Adults with ADHD (n = 31) with stable medication treatment for ADHD and residual symptoms (ASRS > 20) were randomly assigned to DBT‐ST (n = 16) or treatment as usual (TaU; n = 15) for 12 weeks. Feasibility was accessed by attendance and completion rates at 12 weeks. Efficacy outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
1
10
2
Order By: Relevance
“…The effect on self-reported ADHD core symptoms was larger in our study than in other controlled trials based on the same treatment manual [ 28 , 31 , 50 ]. The larger effect size found in our study may be due to slight differences in the actual delivered treatment, i.e.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…The effect on self-reported ADHD core symptoms was larger in our study than in other controlled trials based on the same treatment manual [ 28 , 31 , 50 ]. The larger effect size found in our study may be due to slight differences in the actual delivered treatment, i.e.…”
Section: Discussioncontrasting
confidence: 74%
“…Although these patients were not judged clinically as having a depressive episode that would interfere with treatment, this finding may however motivate future studies to assess the predictive role of depressive symptoms on the effect of this group treatment. The effect on self-reported ADHD core symptoms was larger in our study than in other controlled trials based on the same treatment manual [28,31,50]. The larger effect size found in our study may be due to slight differences in the actual delivered treatment, i.e.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In the remaining 69 works, 50 were excluded because they were non-randomized controlled studies, lack of required data, non-Chinese and non-English works, and meeting abstracts. Finally, 19 RCTs (Amiri et al, 2022; Bachmann et al, 2018; Behbahani et al, 2018; Chen & Cheng, 2016; Converse et al, 2020; Fritz & O’Connor, 2022; Gu et al, 2018; Hepark et al, 2019; Hoxhaj et al, 2018; Janssen et al, 2019; Kiani et al, 2017; Lo et al, 2020; Mitchell et al, 2017; Moritz et al, 2021; Rezaei et al, 2018; Robe & Dobrean, 2022; Schoenberg et al, 2014; Siebelink et al, 2022; Valero et al, 2022) met the inclusion conditions and were synthesized for effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…The language dimension was the most common cultural adaptation reported, with 15 (83%) studies adapting this dimension. Studies reported translating DBT handouts and materials and delivering therapy in Portuguese (Cancian et al, 2019; Moritz et al, 2021), Mandarin (Cheng & Merrick, 2017; Yang et al, 2020), Cantonese (Fan & Leung, 2015), Spanish (Gomez et al, 2017; McFarr et al, 2014; Mercado & Hinojosa, 2017; Montero Fernández et al, 2013; Padilla Torres et al, 2017), and Nepali (Ramaiya et al, 2018). One study specified that language translation included conducting DBT consultation group fully in Spanish (Mercado & Hinojosa, 2017).…”
Section: Resultsmentioning
confidence: 99%